2003
DOI: 10.1002/ana.10753
|View full text |Cite
|
Sign up to set email alerts
|

The expanding mutational spectrum of MERRF substitution G8361A in the mitochondrial tRNALys gene

Abstract: In a case of childhood-onset myoclonus epilepsy with "ragged-red fibers" (MERRF), a hitherto unreported mutation within the mitochondrial tRNA(Lys) gene was identified as the cause of the disease. Substitution G8361A was maternally inherited, heteroplasmic in all tissues tested, and correlated with mitochondrial dysfunction in individual muscle fibers. The growing number of MERRF-associated mutations within the tRNA(Lys) gene affirms the specific role of this mitochondrial tRNA in the pathogenesis of the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
11
2
1
Order By: Relevance
“…After this initial description, other studies have shown that the A8344G mutation is responsible for most cases of MERRF 13 . In the years following the discovery of the A8344G mutation, three additional point mutations have also been found in patients with MERRF in the tRNA Lys gene of mtDNA as follows: T8356C, G8361A and G8363A 14,15,16 . The T8356C Figure 1.…”
Section: What Are the Genetic Abnormalities?mentioning
confidence: 99%
See 1 more Smart Citation
“…After this initial description, other studies have shown that the A8344G mutation is responsible for most cases of MERRF 13 . In the years following the discovery of the A8344G mutation, three additional point mutations have also been found in patients with MERRF in the tRNA Lys gene of mtDNA as follows: T8356C, G8361A and G8363A 14,15,16 . The T8356C Figure 1.…”
Section: What Are the Genetic Abnormalities?mentioning
confidence: 99%
“…point mutation was found in patients with MERRF who also had stroke-like episodes, suggesting an overlap between MERRF and mitochondrial encephalomyopathy with lactic acidosis and stroke-like episodes (MELAS) 16,17 . The A8361G point mutation was described in patients associated with MERRF manifesting with deafness and dementia 14 . The G8363A point mutation appears to be related to the presence of cardiomyopathy and deafness in patients with MERRF, and, in some cases, it overlap with Leigh syndrome 15,18,19,20 .…”
Section: What Are the Genetic Abnormalities?mentioning
confidence: 99%
“…often caused by numerous point mutations (G611A, A3243G, A8344G, G8361A, G12147A) in mtDNA, which affect genes encoding different mitochondrial tRNAs (Mancuso et al, 2004;Mongini et al, 2002;Shoffner et al, 1990;Rossmanith et al, 2003;Melone et al, 2004), is also to some extent associated with lipid-storage disorders and TG accumulation in muscles (MunozMalaga et al, 2000;Naumann et al, 1997). It has also been shown that most of multiple symmetrical lipomatosis (MSL) patients also display mitochondrial dysfunction Berkovic et al, 1991), lipomas that contain atypical multivacuolar white adipocytes (Zancanaro et al, 1990) as well as ragged red fibers and TG accumulation in muscles (Klopstock et al, 1997;Munoz-Malaga et al, 2000).…”
Section: Journal Of Cell Science 119 (7)mentioning
confidence: 99%
“…These findings indicate that there is a respiratory chain dysfunction in the lipomas, and that lipomas may be a manifestation of the A8344G mutation. 58 In tRNA Lys gene four other mutations has also been associated with a typical MERRF phenotype: A8296G, 59 T8356C, 60 G8361A, 61 and G8363A. 59,62 However, the typical MERRF syndrome is not always associated with tRNA Lys mutations.…”
Section: The Clinical Phenotypes Of Mitochondrial Trna Mutationsmentioning
confidence: 99%